2020
DOI: 10.1080/23744235.2020.1744711
|View full text |Cite
|
Sign up to set email alerts
|

A case of imported COVID-19 diagnosed by PCR-positive lower respiratory specimen but with PCR-negative throat swabs

Abstract: A 35-year-old woman presented with fever and mild diarrhoea without any respiratory symptoms 9 days after travelling to Japan from Wuhan, China. Her computed tomography scan revealed pneumonia. The first polymerase chain reaction (PCR) test on throat swab for the novel corona virus upon admission was negative. Therefore, she was treated for communityacquired pneumonia, but fever persisted. On hospital day 5, PCR test on induced sputum was positive, but a second polymerase chain reaction test on throat swab rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 5 publications
1
51
0
4
Order By: Relevance
“…Until now, only some case reports have described the clinical characteristics of patients with persistent negative PCR results from pharyngeal swabs. All of these cases had fever, and patients with nausea also had diarrhea, which was consistent with our ndings that fever was common and nausea was highly correlated with diarrhea [14,[24][25]. In addition, our study also found that patients with both symptoms of dyspnea and chest pain were more common in serology-con rmed cases, possibly due to hypercoagulation status, cardiac injury and involvement of the pleura, as these patients had higher levels of D-dimer and troponin as well as a higher proportion of pleural lesions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Until now, only some case reports have described the clinical characteristics of patients with persistent negative PCR results from pharyngeal swabs. All of these cases had fever, and patients with nausea also had diarrhea, which was consistent with our ndings that fever was common and nausea was highly correlated with diarrhea [14,[24][25]. In addition, our study also found that patients with both symptoms of dyspnea and chest pain were more common in serology-con rmed cases, possibly due to hypercoagulation status, cardiac injury and involvement of the pleura, as these patients had higher levels of D-dimer and troponin as well as a higher proportion of pleural lesions.…”
Section: Discussionsupporting
confidence: 91%
“…However, false negative results were always the most concerning issue, leading to a rapid growth of invention and evaluation of other diagnostic tools such as computed tomography and serum antibody assay [15,18]. In addition, repeated PCR tests of pharyngeal swabs and further specimen collection from the lower respiratory tract were also useful ways to minimize the false negative rate [7,24]. Nevertheless, in our clinical practice and previous case reports [14,[24][25], some symptomatic patients with CT abnormalities were continuously PCR negative for pharyngeal swabs, even with more than three tests, which was enough to detect the majority of PCR-diagnosed patients [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnostic sensitivity of qRT-PCR assay is influenced significantly by the timing of specimen collection during the disease course, site of specimen collection, and skill required during specimen collection [ 6 , 7 ]. It is therefore plausible that a significant proportion of patients with COVID-19 failed to be diagnosed using qRT-PCR [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hase. et al study reported that a COVID-19 case diagnosed by PCR-positive lower respiratory specimen, but with PCR-negative throat swabs [7]. Although the knowledge of viral loads in COVID-19 is limited, the high viral loads of lower respiratory tract specimens had been reported in severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) [8,9].…”
Section: Discussionmentioning
confidence: 99%